Influence of comorbide pathology on the efficiency of laparoscopic operations in surgical treatment of patients with metastatic colorectal cancer - V. E. Kolesnikov; D. V. Burcev (Медицинский вестник Юга России, 2018)
Objective: to determine the eﬀect of the initial comorbid burden in patients with metastatic colorectal cancer (CRC) and resectable liver metastases on the development of postoperative complications, depending on the use of laparoscopic or standard open operations.Materials and Methods: the study included 311 patients with verifed metastatic CRC T3-4N1-2M1 and resectable metastases in the liver. Depending on the organization of the surgical treatment, the patients were divided into two groups: the main group (n=161) performed laparoscopic surgical interventions and a control group (n=150) of patients with the same pathology who underwent traditional open operations. Te comorbidity was assessed by the Charlins comorbidity index, the risk of cardiovascular complications according to Goldman, the adjusted Lee index. Te eﬀect of comorbidity on postoperative complications was studied by the method of constructing conjugacy tables.Results: in patients with metastatic RTC in class IV of the risk of cardiovascular complications according to Goldman and high cardiovascular risk in the Lee index, open surgical interventions had an advantage over laparoscopic surgery because of the risk of life-threatening cardiopulmonary pathology. In the I-III class of the risk of cardiovascular complications according to Goldman and low, as well as intermediate cardiovascular risk in Lee, the laparoscopic operations were not accompanied by an increased risk of postoperative cardiovascular complications and were accompanied, in addition to the traditional advantages of minor trauma, by reducing the complications associated with removal oncological drug, as well as infectious wound complications in the place of surgical intervention. Conclusion: when deciding whether to perform laparoscopic interventions in patients with metastatic CRC and resectable metastases in the liver, it is necessary to assess the comorbid load on the Goldman and Lee index before the operation.